Genetic and molecular analyses for oryza sativa L. cv. MRQ74 frangrance trait through quantitative trait Loci mapping using gene-based and microsatellite markers - Golestan Hashemi, Farahnaz Sadat (2015)
Rice fragrance is a complex trait and one of the aim of rice breeding programs is to improve this quality and to further explore its genetic basis. Grain 2AP (2-acetyl-1- pyrroline) as the primary reason for the distinctive aroma is the most attractive characteristic of high-quality rice. MRQ74, a popular Malaysian aromatic variety, has considerably higher prices than non-aromatic varieties. Thus, breeding this profitable trait has become a priority for Malaysian rice breeding programs. In spite of many studies on aroma genetics, ambiguities about its genetic basis remain. Identifying quantitative trait locus (QTL) based on markers that are associated with candidate genes controlling a trait of interest, can increase the power of QTL detection. This study aimed to locate QTLs that influence natural variations in rice scent using microsatellites and candidate gene-based sequence polymorphisms. For this purpose,an F2 mapping population, including 189 individual plants, was developed through the cross ‘MRQ74’, an elite Malaysian scented cultivar, with ‘MR84’, a Malaysian nonscented cultivar. Qualitative (sensory test) and quantitative (GC-MS) approaches were applied to obtain a phenotype data framework. Totally, 512 pairs of microsatellite primers and six gene-based markers that cover entire rice genome were combined for a comparative polymorphic analysis among the two parents and two randomly selected F1 progenies with 108 markers proving polymorphic for evaluating segregation ratios among the F2 progenies. The observed segregations of each locus were then checked against the expected Mendelian ratio in the segregating population. Results revealed that 88 markers fitted well with 1:2:1 ratio for an F2 population. However, segregation distortion was also found for 20 marker loci that were distributed across 9 chromosomes, except chromosomes 2, 8 and 11. Among these 20 markers, 11 (55%) and 9 (45%) were sloped toward MR84 and MRQ74, respectively. Two QTLs were identified on chromosomes 4 and 8. These QTLs explained from 3.2% to 39.3% of the total fragrance phenotypic variance. In addition, we could resolve linkage group 8 by adding six gene-based primers in the interval harboring the most robust QTL. Hence,we could locate a putative fgr allele in the QTL on chromosome 8 in the interval RM223-SCU015RM (1.63 cM).Developing fragrant rice through marker assisted/aided selection (MAS) is an economical and profitable approach enriching an elite genetic background with a pleasant aroma worldwide. PCR-based DNA markers that distinguish alleles of the main genes of rice fragrance have been synthesized to develop rice scent biofortification by MAS. The present study also examined the aroma biofortification potential of co-dominant markers in the F2 progenies to determine the most influential diagnostic markers for odour biofortification. The SSR as well as functional DNA markers RM5633 (on chromosome 4), RM515, RM223, L06, NKSbad2, FMbadh2-E7, BADEX7-5, Aro7, and SCU015RM (on chromosome 8) were highly associated with 2AP content across the population. The alleles detected via these markers considered for approximately 12.1, 27.05, 27.05, 27.05, 25.42, 25.42, 20.53,20.43, and 20.18% of the total phenotypic variation, respectively. F2 plants harboring the favorable alleles of these effective markers produced higher levels of fragrance. Such rice plants can be used as donor parents to speed up the development of fragrance biofortified tropical rice varieties adapted to growing conditions and consumer preferences, thus contributing to rice global market. Moreover, the identified QTLs represent an important step towards clarification of the rice flavor genetic control mechanism. This identification will accelerate the progress of the use of molecular markers for gene isolation, gene-based cloning, and marker-assisted selection breeding programs aimed at improving rice cultivars.